Critical Thinking Skills of High School Students in Biology Learning on the Concept of Structure and Function of Plant Tissues - Kustiani, Heny; Zaini, Muhammad; Mulyadi, Mulyadi (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
One of the problems faced in education in the 21st century is the critical thinking skills of students who are still considered lacking. One of the learning tools that need to be improved to help improve students' critical thinking skills is the Student Worksheet (LKPD). This study aims to describe the effectiveness of LKPD on the concept of Structure and Function of Plant Tissue Based on Critical Thinking Skills. The validation subjects were 3 experts, individual test subjects were 3 high school class XI students and small group test subjects were 6 class XI high school students. This type of research is development research to produce valid, practical, and effective products. The results showed that the effectiveness of LKPD expectations based on the assessment of students' critical thinking skills in working on LKPD had both categories (including interpretation, analysis, inference, and explanation) and very good categories (including self-regulation). Interpersonal skills (collaborating) and intrapersonal skills (meticulous) students have very good categories.